2018
DOI: 10.1038/s41598-018-24762-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunological responses following administration of a genotype 1a/1b/2/3a quadrivalent HCV VLP vaccine

Abstract: The significant public health problem of Hepatitis C virus (HCV) has been partially addressed with the advent of directly acting antiviral agents (DAAs). However, the development of an effective preventative vaccine would have a significant impact on HCV incidence and would represent a major advance towards controlling and possibly eradicating HCV globally. We previously reported a genotype 1a HCV viral-like particle (VLP) vaccine that produced neutralizing antibodies (NAb) and T cell responses to HCV. To adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 56 publications
(78 reference statements)
0
41
0
2
Order By: Relevance
“…Recently, a HCV-LP system has been established through the transduction of the human hepatoma cell line Huh 7 with recombinant adenovirus encoding the structural genes of HCV [180]. Initially designed using the H77 isolate, further development has expanded by generating HCV-LPs using the structural sequences of different isolates representing Gt1b, 2a and 3a subtypes to produce HCV-LPs with a conformation close to that the wild type virus [180][181][182][183]. Trials of this candidate in mice showed the induction of nAbs and activation of both CD4+ and CD8+ T cell responses and this has recently been reported in a vaccinated Landrace pigs [184].…”
Section: Virus-like Particlesmentioning
confidence: 99%
“…Recently, a HCV-LP system has been established through the transduction of the human hepatoma cell line Huh 7 with recombinant adenovirus encoding the structural genes of HCV [180]. Initially designed using the H77 isolate, further development has expanded by generating HCV-LPs using the structural sequences of different isolates representing Gt1b, 2a and 3a subtypes to produce HCV-LPs with a conformation close to that the wild type virus [180][181][182][183]. Trials of this candidate in mice showed the induction of nAbs and activation of both CD4+ and CD8+ T cell responses and this has recently been reported in a vaccinated Landrace pigs [184].…”
Section: Virus-like Particlesmentioning
confidence: 99%
“…Beveridge book, and in other writings at the boom of implementation of DNA recombinant techniques. Yet, attempts to produce vaccines against highly variable viruses, based on antigenic structures or some viral isolates, are ongoing (Christiansen et al, 2018). A critical issue is if the host immune response against a vaccine engineered with "universal" (conserved) antigenic motifs will be sufficient to prevent disease upon infection by other forms of the same pathogen (Freeman and Cox, 2016).…”
Section: Limitations Of Simplified Reagents and Small Molecules As Anmentioning
confidence: 99%
“…Earlier concerns about neutralizing HCV antibodies being isolate-specific have been assuaged by the demonstration of monoclonal antibodies that cross-neutralize the infectivity of most HCV genotypes that occur around the world (Law et al 2008;Keck et al 2016) and also by rodents (Stamataki et al 2007), chimpanzees (Meunier et al 2011), and human volunteers (Law et al 2013) who were vaccinated with the recombinant E1E2 heterodimeric envelope glycoproteins from a single isolate, but who developed broadly cross-neutralizing antibodies including those targeting important discontinuous epitopes formed by the native interaction of E1 with E2 (Wong et al 2014). Vaccines based on recombinant VLPs or recombinant E2 alone have also been shown to generate some of these cross-neutralizing antibodies (Garrone et al 2011;Vietheer et al 2017;Christiansen et al 2018;Wang et al 2019).…”
Section: Hcv Vaccinementioning
confidence: 99%